WI-FI COMMUNICATION SYSTEM FOR A FIXED-WING TWIN-ENGINE AIRPLANE UAV - BUICAN, George Răzvan; ZAHARIA, Sebastian-Marian (Publishing House of “Henri Coanda” Air Force Academy, 2023)
Unmanned Aerial Vehicle (UAV) systems have automated pilots that can be configured to suit various mission requirements. In this study, we assess, develop, and evaluate a bidirectional Wi-Fi communication link for an automated piloting system, utilizing the Cube Orange architecture that is mounted on a fixed-wing twin-engine airplane UAV. This Wi-Fi link enables seamless data exchange between the UAV and the ground control station. Using this bidirectional communication link, the user gains access to telemetry data, providing real-time insights into the UAV's flight parameters. Additionally, the user can send commands to the UAV, ensuring dynamic mission control and adaptability, while, the Wi-Fi link facilitates the retrieval of live video data from the UAV's onboard camera, enabling display on the command station screen or recording for future analysis and utilization. This comprehensive Wi-Fi communication system enhances the overall functionality and efficiency of the UAV's automated piloting, enabling smooth and reliable operations for various mission scenarios.
his paper was presented at the International Conference of Scientific Research and Education in the Air Force – AFASES 2023, Brașov, Romania. Published in open access by the Henri Coandă Air Force Academy Publishing House. DOI: 10.19062/2247-3173.2023.24.17.
Keywords: Aerospace; Fixed-wing UAV; Automated Pilot; UAV Mission Planning; Additive manufacture